2019
DOI: 10.1080/17482631.2019.1704484
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of fear of childbirth: a metasynthesis of qualitative studies

Abstract: Purpose: Women's experiences of pregnancy, labour and birth are for some pregnant women negative and they develop a fear of childbirth, which can have consequences for their wellbeing and health. The aim was to synthesize qualitative literature to deepen the understanding of women's experiences of fear of childbirth. Methods: A systematic literature search and a meta-synthesis that included 14 qualitative papers. Results: The main results demonstrate a deepened understanding of women's experiences of fear of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 76 publications
7
76
1
5
Order By: Relevance
“…Framed properly, these interrelated positive factors could serve to create an effective characterization of pregnancy and birth as normal and safe, with medical attention and social systems present to support women and keep them healthy through the process, rather than protect or prevent risks. A "safe-supported" rather than a "riskycontrolled" cycle may decrease preconception fear-based perspectives and lead to decreased anxiety and improved outcomes through the pregnancy and birth period (5,7,24). Feeling supported on an individual and societal level may contribute to a sense of safety, conversely allowing women to freely utilize support systems without them becoming a threat to autonomy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Framed properly, these interrelated positive factors could serve to create an effective characterization of pregnancy and birth as normal and safe, with medical attention and social systems present to support women and keep them healthy through the process, rather than protect or prevent risks. A "safe-supported" rather than a "riskycontrolled" cycle may decrease preconception fear-based perspectives and lead to decreased anxiety and improved outcomes through the pregnancy and birth period (5,7,24). Feeling supported on an individual and societal level may contribute to a sense of safety, conversely allowing women to freely utilize support systems without them becoming a threat to autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of negative birthing outcomes or complications among women correlated with higher elective Csection rates and perinatal interventions, negative attitudes toward birthing experience, and more intense labor pains, while pre-birth fear was associated with C-section preference and less positive perceptions of being pregnant (22,24). Clustering by fear, attitudes, and beliefs to understand pre-birth perceptions and decisional preferences demonstrated that fear can impact birth experience (22,24); however, what drives these concerns remains unclear. In Italian populations speci cally, fear of negative outcomes or the unknown has been identi ed as a reason to delay preconception planning (8).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations